Nghiên cứu hoạt hóa bùn đỏ bằng axit sulfuric và khảo sát khả năng hấp phụ Cr(VI) - Dung, Nguyễn Tuấn; Minh, Vũ Xuân; Mỹ, Nguyễn Thanh; Mai Hương, Lê Thị (Vietnam Journal of Chemistry, 2015)
In this study, the red mud from Alumina Tan Rai Plant (M0) is activated by 2 M H2SO4 solution with the ratio of liquid/solid was 1 ml/g (M1) and 2 ml/g (M2). SEM analysis demonstrated the similar morphologies of the three samples, but BET results showed an increase of specific surface area after acid activation. EDX analysis indicated the significantly decrease of the Al, Na and Si contains after activation. Adsorption characteristics of Cr(VI) on red mud surface were investigated in bath, changing various factors such as pH, contact time and Cr(VI) concentration. The results showed that adsorption capacity of activated red mud was much higher than raw red mud, the best removal efficiency obtained at pH 5.6, the adsorption approache the equilibrium after 60 minutes, and the Freundlich isotherm model fits well this process.